Using Arduino to develop research competencies of students in school physics education - Vitalii M. Zadorozhnii (Academy of Cognitive and Natural Sciences, 2024)
Arduino is a popular hardware and software platform that enables the development of various engineering projects, especially in physics and computer science. Arduino can be used as a powerful tool to foster the research competencies of secondary and high school students and stimulate their interest and creativity in science and technology. In this paper, we present some examples of research projects that involve using Arduino in the context of school physics education. These projects include designing and implementing measuring devices and installations for studying physical phenomena, such as uniformly accelerated motion, free fall, pendulum motion, etc. We also show how Arduino can improve existing projects and create new ones based on the students' engineering ideas. We demonstrate the results of the experiments conducted by the students using their Arduino-based devices and discuss the benefits and challenges of using Arduino in school physics education.